2017
DOI: 10.1111/ajd.12632
|View full text |Cite
|
Sign up to set email alerts
|

Effect of atopic dermatitis on quality of life and its psychosocial impact in Asian adolescents

Abstract: Chronic sufferers of severe eczema experience poorer QOL than those with mild or moderate eczema. They also experience significant psychosocial impact as a consequence of their condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 15 publications
1
40
0
Order By: Relevance
“…It is known that the social context of a person's life determines the risk of exposure, as well as their susceptibility, the course and outcome of illness 75,76 . Socio‐economic factors and stressful life events can impact disease control 34,77‐81 and HRQL in allergic diseases 64,70,82,83 . Therefore, the identification and management of socio‐economic issues and stressful life events impacting disease control and HRQL may be recommended (Grade C).…”
Section: Transition Specific To Allergic Conditions And/or Asthmamentioning
confidence: 99%
“…It is known that the social context of a person's life determines the risk of exposure, as well as their susceptibility, the course and outcome of illness 75,76 . Socio‐economic factors and stressful life events can impact disease control 34,77‐81 and HRQL in allergic diseases 64,70,82,83 . Therefore, the identification and management of socio‐economic issues and stressful life events impacting disease control and HRQL may be recommended (Grade C).…”
Section: Transition Specific To Allergic Conditions And/or Asthmamentioning
confidence: 99%
“…A community-based study among Singaporeans demonstrated a high prevalence of atopic dermatitis as well as a low quality of life in adults and children compared with other skin conditions 13 . A more recent study showed that Asian adolescents suffer significant psychosocial impact from this skin condition 12 . It addressed individual domains of quality of life but further analysis of correlated social and clinical factors was not performed due to small sample size 12 .…”
Section: Introductionmentioning
confidence: 99%
“…AD is a multifaced skin disorder with increased prevalence over the world including developed industrialized countries as well as developing countries (Ng et al, 2018, Goh et al, 2018. Deep understanding of cutaneous microbiome using advanced tools seems to provide a better explanation of the potential contributions of AD associated microbial communities in the pathogenesis of AD (Chng et al, 2016).…”
Section: Discussionmentioning
confidence: 99%